Reconciliation of various ideologies in formulating national legislations - a Malaysian experience / Imran Sheik Muhamed … [et al.] - Sheik Muhamed, Imran; Anuar, Muhammad Khairuddin; Suhaimi, Muhammad Syahid; Mohd Aminnudin, Nur Izzati; Bahrin, Amir (2014)
This study revolves around observing and analyzing the nexus between the ideologies that are dominantly present in Malaysia, and its effect towards the formulation of the national legislation. The aim of this study is to reconcile the various ideologies to ensure the co-existence of all the ideologies. This study comprises five chapters in which the first chapter will introduce the anatomy of the study. The second chapter will observe the present state of all the main ideologies. The third chapter is about the interview we have conducted with Prof. Rohimi. The fourth chapter will show the analysis of the interview and other related matters, while the last chapter will conclude the study. This study will act as a humble guide in showcasing the emerging problem of conflict between ideologies in this country and assist the relevant authorities to take action in ameliorating the ideological phenomenon,